2015
DOI: 10.1002/etc.2811
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of dichlorodiphenyltrichloroethane in the benthic polychaete, Nereis succinea: Quantitative estimation by analyzing the partitioning of chemicals between gut fluid and lipid

Abstract: Biotransformation plays an important role in the bioaccumulation and toxicity of a chemical in biota. Dichlorodiphenyltrichloroethane (DDT) commonly co-occurs with its metabolites (dichlorodiphenyldichloroethane [DDD] and dichlorodiphenyldichloroethylene [DDE]), in the environment; thus it is a challenge to accurately quantify the biotransformation rates of DDT and distinguish the sources of the accumulated metabolites in an organism. The present study describes a method developed to quantitatively analyze the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…To more accurately assess sediment risk, many efforts have been made to understand the biotransformation process of xenobiotics in organisms, which is of great importance in chemical bioaccumulation, biomagnification, and toxicity. Wang et al found most DDT transformed to DDD (86%) and DDE (2%) in the benthic polychaete Nereis succinea which considerably changed the composition of bioaccumulative DDT and its transformation products. Recent studies found mercury methylation and demethylation in fish intestine and gut microbial activities were suspected as the driving force, yet there was no direct evidence. , Furthermore, a current-use insecticide, fipronil, was metabolized at similar rates in liver and intestine, implying probable degradation of fipronil by the intestinal microbiota .…”
Section: Introductionmentioning
confidence: 99%
“…To more accurately assess sediment risk, many efforts have been made to understand the biotransformation process of xenobiotics in organisms, which is of great importance in chemical bioaccumulation, biomagnification, and toxicity. Wang et al found most DDT transformed to DDD (86%) and DDE (2%) in the benthic polychaete Nereis succinea which considerably changed the composition of bioaccumulative DDT and its transformation products. Recent studies found mercury methylation and demethylation in fish intestine and gut microbial activities were suspected as the driving force, yet there was no direct evidence. , Furthermore, a current-use insecticide, fipronil, was metabolized at similar rates in liver and intestine, implying probable degradation of fipronil by the intestinal microbiota .…”
Section: Introductionmentioning
confidence: 99%
“…The concentrations of DDT continued to decrease during the toxicity testing. Although DDT is regarded as a persistent organic pollutant, fast degradation of DDT in freshly spiked sediments has also been commonly reported (Hoke et al ; Lotufo et al ; Ding et al ; Wang et al ). As a result, the organisms were actually exposed to a mixture of DDT, DDD, and DDE in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…The extraction was conducted for 3 cycles of 5 min each, with temperature being set at 80 °C and pressure at 1500 psi. The extracts were concentrated by a gentle flow of nitrogen and solvent exchanged to 1 mL of hexane and purified using concentrated H 2 SO 4 (Wang et al 2015). Briefly, 1 mL of concentrated H 2 SO 4 was added to the extracts, and the solution was shaken for 3 min and centrifuged at 2000 rpm for 5 min.…”
Section: Sediment Extraction and Chemical Analysismentioning
confidence: 99%
“…Moreover, the DDD predominance observed in L. culveri tissues is in agreement with the results in N. succinea. The high metabolic capacity to transform DDT in DDD (> 86%) and direct uptake from the sediment would account for this high DDD accumulation in polychaete tissues (Wang et al, 2015). In addition, it could be also related to high excretion and/or avoidance capability to ingest toxic forms of DDTs in sediments (Lotufo et al, 2000;Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The high metabolic capacity to transform DDT in DDD (> 86%) and direct uptake from the sediment would account for this high DDD accumulation in polychaete tissues (Wang et al, 2015). In addition, it could be also related to high excretion and/or avoidance capability to ingest toxic forms of DDTs in sediments (Lotufo et al, 2000;Wang et al, 2015). Moreover, the predominance of DDD in SWA estuarine sediments suggests higher DDT dechlorination to DDD under anaerobic conditions due to the characteristics of these muddy sand sediments (Lin et al, 2009).…”
Section: Discussionmentioning
confidence: 99%